Sockeye salmon of Iturup Island: characteristics of spawners from commercial catches in 2021 - A. N. Elnikov; O. V. Zelennikov (Известия ТИНРО, 2022)
Spawners of sockeye salmon caught in northern Iturup and in the Prostor Bay and Kurilsky Bay in July-August, 2021 are investigated. Almost all of them had the age 1.2+ or 1.3+, with prominent prevalence of the former both for females (88.9 %) and males (80.0 %); other age groups had symbolic representation. Older individuals of both sexes were significantly larger. The sockeye of Iturup Island spend only 2 years in the sea, so both females and males are smaller by weight than the producers of other sockeye herds in the Russian Far East. The short puberty is supposedly favorable for formation of relatively abundant stock of artificial reproduction by the sockeye of Iturup Island.